Effect of in ovo creatine monohydrate on hatchability, post-hatch performance, breast muscle yield and fiber size in chicks from young breeder flocks - Corey-Ann B. Firman; Vivienne Inhuber; David J. Cadogan; William H.E.J. Van Wettere; Rebecca E.A. Forder (Poultry Science, 2023)
ABSTRACT: Younger broiler breeder flocks produce smaller eggs containing smaller yolks, with potentially lower energy reserves for the developing chick. Creatine is a naturally occurring energy source and is abundant in metabolically active tissues; providing this to chicks in ovo should provide additional energy to improve hatchability and post-hatch growth. Thus, post-hatch performance of male and female chicks hatched from younger breeder flocks supplemented with creatine monohydrate (CrM) in ovo was investigated. Four hundred eggs from Ross 308 breeder hens aged 27 to 29 wk were collected and at d 14 assigned to a treatment group and received 1) no injection, 2) 0.75% saline injection, or 3) 8.16 mg creatine monohydrate in 0.75% saline. At hatch 72 birds (24/treatment) were euthanized and BW, breast muscle, heart and liver weight were obtained, and breast muscle tissue was placed in 10% buffered formalin. Birds were then placed in raised metal pens (24 pens; 10–11 birds/pen; 8 replicates/treatment) and grown to d 42 with BW and pen feed intake measured once a week. At d 42, ninty-six birds were euthanized (2 male and 2 female/pen) and the process occurred as at hatch. Body composition was obtained for 48 birds (2/pen; 1 male,1 female) with a dual energy X-ray absorptiometry (DXA) scanner. Breast muscle tissue was processed for histological analysis and breast muscle fiber parameters were analyzed by ImageJ. While not statistically significant, the CrM treatment group saw an improved hatch rate (CrM: 93.5%, Saline: 88.6%, Control: 88.8%) and reduced early post hatch mortality. Chicks given in ovo CrM had significantly increased creatine concentrations in both liver and heart tissue at hatch compared to those in the saline and control groups. BW, BW gain, and final body composition parameters were not statistically different between treatments and in ovo CrM did not affect breast muscle fiber number or area. The creatine injection likely improved the energy status of the growing embryo resulting in the improved hatch rate but leaving little reserves for post-hatch growth.